Development of Standard Early Detection Instrument Suspected Pulmonary Tuberculosis in Family With Positive Pulmonary Tuberculosis - Fitriana, Noorma; Isnaeni, Wiwi; Khumaedi, M. (Journal of Research and Educational Research Evaluation, 2018)
Tuberculosis or TB is a contagious infectious disease caused by the Mycobacterium tuberculosa bacillus. Suspect pulmonary tuberculosis is a person who has signs and symptoms of pulmonary TB. The diagnosis of pulmonary TB can be established based on clinical symptoms, physical examination and bacteriologic examination. This study aims to develop a standard instrument of suspected pulmonary TB in families with positive pulmonary tuberculosis. The method used in this research is the development of an instrument that refers to the development of Djemari Mardapi model with 9 steps of development. This research was conducted with 3 stages. The first stage is the preliminary stage, then the development stage and last is the evaluation stage. Instrument review by expert or content validity was analyzed using Aiken V formula, instrument reliability based on agreement of experts analyzed using Two Way Anava and reanalyzed using Hoyt formula. The construct validity was analyzed using Exploratory Factor Analysis (EFA) with the help of SPSS 18.0 software, while instrument reliability based on field results was analyzed using KR-20 formula. The results of the content validity indicate that twenty-six instrument items have values >0.3 which means that all valid instrument items are used. The result of reliability based on expert agreement shows the value of 0.824 which means experts agree in judging. The result of construct validity is Kaiser Meyer Olkin (KMO) 0,816, Measure Sampling Adequacy (MSA) >0,5, and Bartlett's test 0,000 significance test so that instrument item can be analyzed further. There are 5 factors formed from the 26 available instrument items and each item in each factor has a factor loading value> 0.3. Instrument reliability results using KR-20 formula of 0.929, which means reliable instrument used. Based on the evaluation of standard instrument of early detection of pulmonary tuberculosis suspect developed, overall 26 instrument items able to measure indicator of variable to be measured. Further developed instruments can be used by health workers and cadres to perform suspect pulmonary tuberculosis in the community.